The role of Zakat on Muslims’ tax compliance behavior – from qualitative perspectives - Abdullah, M. (2017)
Tax compliance has always been an issue ever since the existence of tax. Various theories and models have been proposed and introduced in the literature to assist governments, tax agencies and relevant authorities to encourage voluntary compliance behaviour or to discourage non-compliance attitudes. In tax compliance literature, zakat has not been explicitly considered as one of the factors that might affect tax compliance. This study aims to explore the role played by zakat and provide the framework for encouraging tax compliance among Muslims taxpayers. This study is based on interviews with Muslims taxpayers in Malaysia and a review of literatures. This qualitative analysis contributes to different views of tax compliance issues and adds to the extant literature on zakat and tax compliance. Practically, the proposed framework can be tested empirically by future research and this would enhance our understanding on the role zakat on Muslims’ tax compliance behaviour.